Pengaruh Penerapan Model Teams Games Tournament Berbasis Baamboozle Terhadap Kemampuan Berpikir Kritis Matematika Kelas IV SD - Azizah, Richia Deha; Hermawan, Jody Setya; Erni; Destini, Frida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low mathematical critical thinking ability of fourth grade elementary school students. The research aimed to examine the effect of the Teams Games Tournament learning model assisted by Baamboozle media on students’ mathematical critical thinking skills. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The population consisted of all fourth grade students, while the sample was divided into an experimental class and a control class. The experimental class received instruction using the Teams Games Tournament model assisted by Baamboozle, whereas the control class was taught using conventional learning. Data were collected through a critical thinking test administered before and after treatment. The results showed a significant improvement in students’ mathematical critical thinking skills in the experimental class compared to the control class. The average posttest score and N-Gain value in the experimental class were higher, indicating that the implementation of the Teams Games Tournament model supported by interactive game-based media created a more active learning environment and encouraged student participation in problem solving. Therefore, the Teams Games Tournament learning model assisted by Baamboozle has a positive effect on improving elementary students’ mathematical critical thinking ability.